2010
DOI: 10.1177/0960327110372647
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of aqueous extract of Aloe ferox Mill. in loperamide-induced constipated rats

Abstract: Aloe ferox Mill. is a widely used medicinal plant in South Africa for the treatment of many ailments including constipation. The present study evaluated the toxicological effect of aqueous leaf extract of the herb at 50, 100 and 200 mg/kg body weight for 7 days on the haematological parameters as well as liver and kidney function indices in loperamide—induced constipated rats. The extract did not cause any significant (p > 0.05) effect on the kidney and liver—body weight ratio as well as the kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…The reduction in these indices may be direct consequences of the significant decreases in the feed and water intakes resulting from loperamide exposure. This agrees with the report of Wintola et al (2010aWintola et al ( , 2010b, where reduced faecal features in drug-treated rats were attributed to loss of appetite and sharp reduction in the feeding patterns resulting from accumulated faecal pellets in the gastrointestinal tract. Conversely, the concentration-dependent reversion in the faecal properties following treatment with ethanol root extract of M. serrata is suggestive of its laxative potential.…”
Section: Laxative Activitysupporting
confidence: 82%
See 1 more Smart Citation
“…The reduction in these indices may be direct consequences of the significant decreases in the feed and water intakes resulting from loperamide exposure. This agrees with the report of Wintola et al (2010aWintola et al ( , 2010b, where reduced faecal features in drug-treated rats were attributed to loss of appetite and sharp reduction in the feeding patterns resulting from accumulated faecal pellets in the gastrointestinal tract. Conversely, the concentration-dependent reversion in the faecal properties following treatment with ethanol root extract of M. serrata is suggestive of its laxative potential.…”
Section: Laxative Activitysupporting
confidence: 82%
“…the application of these plants rested largely on the assumption that they are safe and devoid of side effects (Wintola et al 2010a(Wintola et al , 2010b. Accordingly, limitations on the general acceptability of herbal medicines due to lack of standardized chemical characterization, dosage regimen and substantial toxicity profile to ascertain their safety needs concerted attention (Pousset 1988).…”
Section: Discussionmentioning
confidence: 99%
“…(Aspodelaceae) 0.05À0.2; aqueous leaves extract.7-days study (Rat) South Africa Safe: AST a , ALT a , ALP a , GGT a , TP a , ALB a , TBL a , BUN a , CRE a , UA a , K 1a , Ca 21a[182].…”
mentioning
confidence: 99%
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) (Shimotoyodome et al, 2000;Wintola et al, 2010Wintola et al, , 2011 (Kakino et al, 2010;Kakino et al, 2012;Kim et al, 2013;Meite et al, 2010;Wintola et al, 2010Wintola et al, , 2011Wu et al, 2010;Wu et al, 2011), though there is limited information on the pharmacokinetics of aqueous plant extracts or traditional Chinese formula under constipated conditions. Additionally, investigations on the comparative pharmacokinetic profiles of drugs with the various body conditions have been reported (Dai et al, 2014;Feng et al, 2013;Han et al, 2013;Zhu et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…These results indicated that the loperamide inhibits intestinal water secretion and colonic peristalsis. This inhibition extends fecal evacuation time and delays intestinal luminal transit (Shimotoyodome et al, 2000;Wintola et al, 2010Wintola et al, , 2011. In order to investigate whether pharmacokinetic profiling of rhein is be altered under constipation, the pharmacokinetics of rhein in normal and constipated rats was investigated.…”
Section: Comparative Pharmacokinetics Of Rhein In Normal and Constipamentioning
confidence: 99%